A comparative study in the use of topical mitomycin-C versus nasolacrimal stent in endoscopic dacryocystorhinostomy for chronic dacryocystitis - Gupta, Vikas; Singh, Inderdeep; Dwivedi, Gunjan; Goyal, Sunil; Kumar, Manoj; Sood, Amit; Upadhyay, Madhukar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Inflammation of the lacrimal sac and duct is a common and unpleasant condition, leading to troublesome epiphora and recurrent dacryocystitis. Surgery is the preferred treatment modality of chronic dacryocystitis which can be performed by external approach or endoscopic nasal approach. Endoscopic dacrycocystorhinostomy (EnDCR) is now a well-established procedure to relieve nasolacrimal duct obstruction, becoming ENT surgeons’ domain. The aim of this study is to assess the efficacy and compare results of intraoperative use of nasolacrimal stent in comparison of mitomycin-C (MMC) in endoscopic dacryocystorhinostomy. Methods: A prospective study of 56 patients with acquired NLDO with epiphora and recurrent dacryocystitis who were evaluated and managed between Oct 2014 and Oct 2016. All patients were offered surgical line of management by endoscopic route. They were randomly assigned into two groups-mitomycin-C group (Group A) and silastic nasolacrimal stenting (Group B). 46 patients who matched inclusion criteria’s were included in the study after formal evaluation by ENT surgeon and Ophthalmologist. 26 patients underwent endoscopic dacryocystorhinostomy with Mitomycin-C application intra – op, 20 patients underwent nasolacrimal silicone stent placement. Results: At 6-month follow-up visit, the management was considered successful if the lacrimal sac irrigation succeeded with relief of symptoms. The success rate in Group A was 92.30%. Group B had 85% success rate. However, no significant (p value=0.37) was noticed between two groups. Conclusions: Despite, no significant difference in outcome between two modalities, there is a trend towards the better outcome with use of mitomycin-C. Mitomycin-C is a safe, effective, and economical adjuvant in endoscopic DCR assisting in improved outcomes of surgery.